EVALUASI PRODUKTIVITAS EXCAVATOR PADA PENGUPASAN OVERBURDEN DI PT DIZMATRA POWERINDO LAHAT SUMATERA SELATAN - Ahmad Husni (Ensiklopedia of Journal, 2026)
The mining sector is a capital-intensive, technology-intensive, and high-risk industry. One of the main activities that significantly influences the continuity of coal production is overburden removal. This study aims to evaluate the productivity of Komatsu excavators in overburden removal activities at PT Dizamatra Powerindo, Lahat, South Sumatra, and identify the factors that influence it. The research methods used include collecting primary and secondary data through field observations, measuring work cycle times (time study), recording bottleneck times, documentation, and literature studies. Primary data include work cycle time, number of cycles per hour, work front conditions, bucket fill factor, bottleneck time, and work efficiency of equipment and operators. The results show that the actual productivity of the Komatsu PC 1250 excavator of 542,029 BCM/hour has exceeded the company's target of 500 BCM/hour, with an estimated monthly production of 357,739 BCM. The main factors that influence productivity include work cycle time, bucket fill factor, work front conditions, loading patterns, material swell factor, and operational and mechanical bottleneck times. Furthermore, the geometry of the work surface and operator skills also play a crucial role in ensuring the smooth operation of the excavation and loading process. Therefore, excavator productivity in overburden removal activities is greatly influenced by a combination of equipment technical condition, field conditions, and mine operational management.Keywords: excavator productivity, overburden removal, digging and loading equipment, open pit mining, work efficiency